The Progress of Immune Cells-induced Inflammatory Response in Gout - Liu, Jing; Liu, Ge; Chu, Teng; Wu, Yue; Yang, Lele Zixin; Fang, Weirong (Current Pharmaceutical Design, 2025)
Gout, based on hyperuricemia, is an immune disease characterized by redness and pain caused by monosodium urate (MSU) deposition in the joints. Inflammation is the fundamental cause of gout symptoms, and many immune cells, such as monocytes/macrophages, neutrophils, and T lymphocytes, have been shown to be involved in various processes of pathological progress. This study reviews the changes and functions of different immune cells during the occurrence and development of gout, focusing on the mechanisms and signaling pathways by which macrophages activate nod-like receptor pyrin-containing 3 (NLRP3) inflammasome to initiate gout inflammation in order to further elucidate the pathogenesis of gout and provide new targets for the research of anti-gout drugs.
Keywords: immunology